DIFFERENTIAL PROTEIN PATTERN IN CERVICAL MUCUS AND BLOOD SERUM OF NORMAL FERTILE AND REPEAT BREEDER KANKREJ CATTLE - MODI, L C; SUTHAR, B N; CHAUDHARY, S; MODI, F (The Indian Journal of Animal Reproduction, 2016)
The cervical mucus and blood serum of normal fertile (n=10) and repeat breeder (n=20) Kankrej cattle revealed 8 to 10 protein bands by SDS-PAGE. The cervical mucus of repeat breeder cattle contained proteins of comparatively higher molecular weight than their normal fertile counterparts, whereas, the serum of normal fertile cattle contained proteins of higher molecular weight than the repeat breeder Kankrej cattle.
Keywords: Blood serum; Cattle; Cervical Mucus; Repeat breeder; SDS-PAGE